Generic versus brand-name over-the-counter analgesics: knowledge and attitudes among Swedish pharmacy customers - Helle Håkonsen; Maria Wängberg; Dina Alani; Tove Hedenrud (Taylor & Francis Group, 2020)
Background Due to a liberalisation reform in 2009, the availability of over-the-counter (OTC) analgesics has increased significantly in the Swedish market over the past decade. With the increasing number of generic products available on the market and the possibility of buying OTC drugs from non-pharmacy outlets, a key to safe drug use is that consumers possess the necessary knowledge to differentiate between the different brands and choose the appropriate drug for their ailments. The aim of this study was to investigate Swedish consumers' knowledge of and attitudes towards generic OTC analgesics. Methods A sample of 209 Swedish adults (66% women; mean age 43.1 years) who bought OTC analgesics at a community pharmacy in one of the country's three largest cities responded to a structured questionnaire. The questions related to knowledge of active substances, the use and choice of OTC analgesics (generic or original brand), attitudes towards generic OTC analgesics, information received about OTC analgesics and experience with generic substitution of prescription drugs. Results Almost one in five reported weekly use of OTC analgesics, and 32% assigned minimum three out of four active substances to the correct brand(s) of OTC analgesics. Among the 50 participants (24%) who assigned all four active substances correctly, it was predominantly women and participants with higher education. Four out of five participants were positive towards the cheaper brands, and 69% reportedly chose cheaper generic brands over more expensive brands. Knowledge about the active substances of different brands was associated with positive attitudes towards generic products. Conclusion Swedish pharmacy customers have to a varying extent the knowledge to differentiate between different brands of commonly used OTC analgesics in terms of active substances. There is a predominantly positive attitude towards generic OTC analgesics, although some consider generic drugs to be inferior and stay loyal to the original brands.